2023
DOI: 10.1080/21505594.2023.2250065
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and transmission characteristics of clade 2.3.4.4b H5N6 subtype avian influenza viruses possessing different internal gene constellations

Wanchen Zhao,
Xin Liu,
Xinyu Zhang
et al.

Abstract: Clade 2.3.4.4 H5N6 avian influenza virus (AIV) has been predominant in poultry in China, and the circulating haemagglutinin (HA) gene has changed from clade 2.3.4.4h to clade 2.3.4.4b in recent years. In 2021, we isolated four H5N6 viruses from ducks during the routine surveillance of AIV in China. The whole-genome sequencing results demonstrated that the four isolates all belonged to the currently prevalent clade 2.3.4.4b but had different internal gene constellations, which could be divided into G1 and G2 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…One report showed that H3N8 in wild birds possessed dual-receptor binding properties in the HA protein, which supports the occurrence of this type of AIV interspecies transmission (Tian et al, 2023). Notably, studies had shown that H3NX AIV has the ability to provide genetic fragments for reassortment in other subtypes of influenza viruses, leading to the production of new highly pathogenic strains and thus to influenza outbreaks (Peng et al, 2013;Wenqiang et al, 2017;Zhao et al, 2023). The H3-subtype AIV can also undergo recombination to alter its pathogenicity and has the potential to break through the interspecific barrier to infect humans (Song et al, 2008).…”
Section: Introductionmentioning
confidence: 92%
“…One report showed that H3N8 in wild birds possessed dual-receptor binding properties in the HA protein, which supports the occurrence of this type of AIV interspecies transmission (Tian et al, 2023). Notably, studies had shown that H3NX AIV has the ability to provide genetic fragments for reassortment in other subtypes of influenza viruses, leading to the production of new highly pathogenic strains and thus to influenza outbreaks (Peng et al, 2013;Wenqiang et al, 2017;Zhao et al, 2023). The H3-subtype AIV can also undergo recombination to alter its pathogenicity and has the potential to break through the interspecific barrier to infect humans (Song et al, 2008).…”
Section: Introductionmentioning
confidence: 92%
“…Sequences got downloaded and further analyzed using MEGA X Analysis software (Kumar, Stecher, Li, Knyaz, and Tamura 2018). The alignment was fed with additional, related sequences from 18,40 . Sequences were nally aligned using MUSCLE and audited.…”
Section: Phylogenetic Analysismentioning
confidence: 99%